ANALISIS EFESIENSI PRODUKSI PETANI SAYURAN DI KABUPATEN SIAK - Helvernando Panjaitan; Djaimi Bakce; Deby Kurnia (Indonesian Journal of Agricultural Economics, 2020)
The objective of this research is to analyze the efficiency of vegetable production. This research uses Data Envelopment Analysis (DEA) method which is the non-parametric method based on Linear Programming. The survey results show that vegetable farmers in Siak Regency have not done standard cultivation techniques. Most vegetable farms use excessive production factors. Based on the analysis of production efficiency can be concluded that: First, most vegetable farming is not technically efficient, because the farming techniques that farmers do not match the standard cultivation techniques. Second, most vegetable farming is also inefficiently allocative, due to the excessive use of inputs, especially in the use of seeds and the use of inorganic fertilizers and the high ratio of input prices to output prices. Third, most technically inefficient and allocative vegetable farms indicate that most vegetable farming is not economically efficient. Economically efficient vegetable farming system can be realized with government assistance to support farmers to make vegetable farming in accordance with the standards of vegetable farming techniques. Furthermore, it is necessary to control the input price and increase the output price.